2021
DOI: 10.1038/s41598-021-03680-3
|View full text |Cite
|
Sign up to set email alerts
|

The weak evidence of lip print analysis for sexual dimorphism in forensic dentistry: a systematic literature review and meta-analysis

Abstract: This study aimed to assess the prevalence of lip print patterns among males and females, and to test the diagnostic accuracy of lip pattern analysis for sexual dimorphism in forensic dentistry. A systematic literature review was performed following the PRISMA guidelines. The search was performed in six primary databases and three databases to cover part of the grey literature. Observational and diagnostic accuracy studies that investigated lip print patterns through cheiloscopy for sexual dimorphism were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Furthermore, the studies have limited sample sizes (understandably because these studies were difficult to conduct), [59][60][61] and Franco et al found that most of the studies on cheiloscopy were highly heterogenous, generally observational and cross-sectional with a lack of standardisation in methodology, which could have incorporated greater error into the findings. 57 The pooled accuracy was 76.8% and the authors concluded that cheiloscopy is not a reliable tool in forensic practice for sex estimation. 57 In forensic practice, cheiloscopy involves obtaining a lip print from the individual and then comparing the print to a known source.…”
Section: Cheiloscopymentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the studies have limited sample sizes (understandably because these studies were difficult to conduct), [59][60][61] and Franco et al found that most of the studies on cheiloscopy were highly heterogenous, generally observational and cross-sectional with a lack of standardisation in methodology, which could have incorporated greater error into the findings. 57 The pooled accuracy was 76.8% and the authors concluded that cheiloscopy is not a reliable tool in forensic practice for sex estimation. 57 In forensic practice, cheiloscopy involves obtaining a lip print from the individual and then comparing the print to a known source.…”
Section: Cheiloscopymentioning
confidence: 98%
“…57 The pooled accuracy was 76.8% and the authors concluded that cheiloscopy is not a reliable tool in forensic practice for sex estimation. 57 In forensic practice, cheiloscopy involves obtaining a lip print from the individual and then comparing the print to a known source. One major disadvantage of using lip prints for sex estimation in dental profiling is that the usefulness of cheiloscopy heavily depends on the lips being intact at the time of post-mortem examination.…”
Section: Cheiloscopymentioning
confidence: 98%
See 1 more Smart Citation
“…Dental evidence has been studied for several forensic purposes over the years. Expect human identification, bite mark analysis, 20 anthropological estimation of age, 21 sex, 22 stature, 23 and ancestry, 24 rugoscopy, 25 and cheiloscopy 26 currently represent fields of forensic odontology 27 . (b) Tooth development results from the epithelial‐mesenchymal interaction, and tooth development consists of three parts: bud stage, cap stage, and bell stage 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Expect human identification, bite mark analysis, 20 anthropological estimation of age, 21 sex, 22 stature, 23 and ancestry, 24 rugoscopy, 25 and cheiloscopy 26 currently represent fields of forensic odontology. 27 (b) Tooth development results from the epithelial-mesenchymal interaction, and tooth development consists of three parts: bud stage, cap stage, and bell stage. 28,29 Odontoblast secretes noncollagenous proteins, including dentin sialophosphoprotein (DSPP) and dentin matrix protein 1 (DMP1).…”
Section: The Burst Abstractmentioning
confidence: 99%